1990
DOI: 10.1093/nar/18.3.501
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of polyamide-oligonucleotide probes containing multiple non-radioactive labels

Abstract: Oligonucleotide probes containing multiple non-radioactive labels have been prepared by utilising and extending the methods used to prepare polyamide-oligonucleotide conjugates. The probes were prepared by incorporating suitable amino acid residues, such as lysines, in the polyamide, which were then used as sites for the attachment of the non-radioactive labels. The procedures developed give control over the distance of the label from the oligonucleotide, and also the inter-label distance. The labels can be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 9 publications
1
49
0
Order By: Relevance
“…To compensate for the low inherent absorbance of lanthanide ions, the luminescent probes contain an antenna fluorophore, which absorbs the light and transfers the energy to a tethered Ln 3+ ion that finally emits the light [3 and references therein]. One of the ways to significantly increase the detection sensitivity of light-emitting probes is to bundle them onto a carrier molecule, which then can be attached to an object of interest [10-11]. With conventional fluorophores this approach is complicated due to self-quenching, which is facilitated by the fluorescence resonance energy transfer (FRET) from an excited to a nearby non-excited dye molecule that efficiently absorbs the energy [10-11].…”
Section: Introductionmentioning
confidence: 99%
“…To compensate for the low inherent absorbance of lanthanide ions, the luminescent probes contain an antenna fluorophore, which absorbs the light and transfers the energy to a tethered Ln 3+ ion that finally emits the light [3 and references therein]. One of the ways to significantly increase the detection sensitivity of light-emitting probes is to bundle them onto a carrier molecule, which then can be attached to an object of interest [10-11]. With conventional fluorophores this approach is complicated due to self-quenching, which is facilitated by the fluorescence resonance energy transfer (FRET) from an excited to a nearby non-excited dye molecule that efficiently absorbs the energy [10-11].…”
Section: Introductionmentioning
confidence: 99%
“…In a different approach, Haralambidis et al [77][78][79][80] reported the derivatization of aminopropylated-CPG with the peptide (Ala-Lys-)sAla (as in 52) toward the preparation of peptideoligodeoxyribonucleotide conjugates. This strategy would also permit the attachment of non-radioactive labels to the lysine residues of the conjugates.…”
mentioning
confidence: 99%
“…The Tb 3+ chelate is multiply labeled onto the probe DNA by using the streptavidinbiotin interaction, and causes strong sensitized emission of Cy3. Such multiple labeling strategy was not effective for enhancing the fluorescence of the acceptor in the conventional donor organic dye system, due to π-stacking and reabsorption of the emitted fluorescence of the donor (18). The Tb 3+ chelate molecules do not stack to each other and do not quench their emission since they have a large Stokes shift.…”
Section: Resultsmentioning
confidence: 99%